Assessment of the suitability of different cassava varieties for gari and fufu flour production in Liberia - Awoyale, W.; Asiedu, R.; Kawalawu, W.K.; Abass, A.; Maziya-Dixon, Busie; Kromah, A.; Edet, M.; Mulbah, S. (Sciencedomain International, 2020)
Different cassava varieties are available in Liberia, but there is little knowledge of their product suitability. Hence, the need to assess the potentials of these varieties to produce gari and fufu flour. The two products from ten improved and two local cassava varieties were characterized based on their yield and chemical, pasting and functional properties using standard methods. The results showed that TMS 96/0097 (gari 27.54%) and Butter cassava (fufu flour 27.35%) have the highest percentage yields. The starch content was higher in gari produced from TMS98/0505 (92.00%) and lower from TMS95/0289 (82.62%); the fufu flour starch content was higher in TMS98/0505 (90.59%) and lower in Bassa girl (84.75%). Gari and fufu flour produced from TMS96/0097 (507.38 RUV) and TMS00/0357 (506.04 RVU) had the highest final viscosity, and the products from TMS95/0289 (338.46 RVU and 336.80 RVU) had the least. The highest swelling power was found in gari (12.74%) and fufu flour (13.55%) produced from TMS92/0057 and the lowest in TMS91/0416 gari (8.23%) and TMS01/1235 fufu flour (8.31%). All the samples may form a paste below the boiling point of water (100°C) at < 7 min. However, cassava varieties and the interactions between varieties and locations had a significant (P < 0.05) effect on the properties of the products: Chemical (except ash content), pasting (except pasting temperature) and functional. Therefore, all the varieties may be suitable for gari and fufu flour production based on the quality preferred by the consumers.